Analisis Kesesuaian dan Daya Dukung Kawasan Wisata Bahari Teluk Urfu, Kabupaten Biak Numfor - Lisiard Dimara; Agustinus Renyoet (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2020)
Urfu Bay is one of the new marine tourism destinations among the Biak Numfor community. This tourist area does not yet have data from scientific studies related to the level of suitability of the region and its environmental carrying capacity, so it is considered necessary to do so. It is feared that the unavailable accurate data about the condition of tourist areas can pose risks to the comfort and safety of visitors, considering these two aspects are the main reference in the management and development of a tourist area. The purpose of the research is: (1) to know the level of conformity of Urfu Bay area as a marine tourism area, and (2) to know the carrying capacity of urfu bay marine tourism area. The research took place from July to September 2020 in the marine tourism area of Urfu Bay, Biak Numfor Regency. The research methods used are surveys with random sampling techniques, observations, interviews, and library studies. The results showed: [1] Urfu Bay marine tourism area is not suitable for coastal recreation activities (1,235) and diving (1,370), while it is suitable for snorkeling tourism activities (2,285), and [2] the carrying capacity of the urfu bay marine tourism area is 176 people per day. The conclusion of this research is that the coastal area of Urfu Bay is not suitable for marine/coastal tourism activities.Keywords: Suitability; Carrying Capacity; Marine Tourism; Urfu Bay; Biak Numfor